A large Bayesian vector autoregression model for Russia - Elena Deryugina; Alexey Ponomarenko (Bank of Finland, Institute for Economies in Transition (BOFIT), 2014)
We apply an econometric approach developed specifically to address the 'curse of dimensionality' in Russian data and estimate a Bayesian vector autoregression model comprising 14 major domestic real, price and monetary macroeconomic indicators as well as external sector variables. We conduct several types of exercise to validate our model: impulse response analysis, recursive forecasting and counter factual simulation. Our results demonstrate that the employed methodology is highly appropriate for economic modelling in Russia. We also show that post-crisis real sector developments in Russia could be accurately forecast if conditioned on the oil price and EU GDP (but not if conditioned on the oil price alone). Publication
URN:NBN:fi:bof-201412193432
Keywords: E32; E44; E47; C32; 330; Bayesian vector autoregression; forecasting; Russia